O. Romuald Gustaw OFM – założyciel Ośrodka Archiwów Bibliotek i Muzeów Kościelnych - Hamryszczak, Artur (Archiwa, Biblioteki i Muzea Kościelne, 2016)
Fr Romuald Gustaw OFM, a long-time Director of the Catholic University of Lublin (KUL) Library, inspired the creation of the Institute of Church Archives, Libraries and Museums. Due to his competence, at the request of Cardinal Stefan Wyszyński, he organized training courses for employees of church libraries. Then the decision was also made to establish an institute (attached to the KUL Library), which could deal with church libraries, and eventually archives and museums. In 1956, Fr R. Gustaw presented the project of creating such an institute to the Polish Episcopate. On 20 December 1956, the authorities of the Catholic University of Lublin, at his request, approved the creation of the Institute of Church Archives, Libraries and Museums as a department of the KUL Library. In 1958, after the institute had become an independent centre, Fr R. Gustaw was appointed as manager of the library section; and he held this function until his death. In 1957, he was the initiator of creating the journal of the institute "Archiwa Biblioteki i Muzea Kościelne". In the years 1961-1972, he was a member of the editorial board. The volume 23 of 1971 was dedicated to Fr R. Gustaw on the occasion of the 60th anniversary of his birth and 20 years of his work as the Director of the KUL Library.